2006
DOI: 10.1111/j.1471-4159.2006.04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐synuclein inhibits aromatic amino acid decarboxylase activity in dopaminergic cells

Abstract: Alpha-synuclein is a presynaptic protein strongly implicated in Parkinson's disease (PD). Because dopamine neurons are invariably compromised during pathogenesis in PD, we have been exploring the functions of alpha-synuclein with particular relevance to dopaminergic neuronal cells. We previously discovered reduced tyrosine hydroxylase (TH) activity and minimal dopamine synthesis in stably-transfected MN9D cells overexpressing either wild-type or A53T mutant (alanine to threonine at amino acid 53) alpha-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 65 publications
5
73
0
1
Order By: Relevance
“…Equal aliquots of cell extracts were then used for co-IP for TH using a pan-TH antibody or for 14-3-3 using a pan-14-3-3 antibody. A representative autoradiographic image confirms 32 P signal of TH at 60 kDa in the TH co-IP and also in the parallel 14-3-3 co-IP, confirming that 14-3-3 binds to phosphorylated TH in midbrain-derived MN9D neuronal cells. Molecular weights (M r ), determined from prestained standards, are shown on the left.…”
Section: Multiple 14-3-3 Isoforms Are Present In Similar Relative Amosupporting
confidence: 63%
See 1 more Smart Citation
“…Equal aliquots of cell extracts were then used for co-IP for TH using a pan-TH antibody or for 14-3-3 using a pan-14-3-3 antibody. A representative autoradiographic image confirms 32 P signal of TH at 60 kDa in the TH co-IP and also in the parallel 14-3-3 co-IP, confirming that 14-3-3 binds to phosphorylated TH in midbrain-derived MN9D neuronal cells. Molecular weights (M r ), determined from prestained standards, are shown on the left.…”
Section: Multiple 14-3-3 Isoforms Are Present In Similar Relative Amosupporting
confidence: 63%
“…A. Heller and L. Won, University of Chicago) express abundant TH, synthesize DA, and also quantally release DA (28 -30). Low-passage cells were grown on TPP plates (LPS, Rochester, NY) in Dulbecco's modified Eagle's medium (D5648; Sigma) and 10% fetal bovine serum (Hyclone, Logan, UT) at 37°C as previously described (28,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…4C), suggesting that DJ-1 stimulates TH activity without causing modification of TH. It has been reported that ␣-synuclein was associated with DDC and inhibited DDC activity in dopaminergic cells (23). Because DJ-1 inhibits aggregation of ␣-synuclein (16), it is interesting that DJ-1 and ␣-synuclein mutually antagonize their functions in dopamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Activities of Tyrosine Hydroxylase and L-Dopa Decarboxylase in Cells-TH and DDC activities in cells were measured according to the published method using HPLC (16,23). The HPLC system and column used were AKTA explorer 10 S/100 (GE Healthcare), COSMOSIL Cholester Waters (4.6 ϫ 150 mm, Nacalai Tesque, Kyoto, Japan), and the buffer used was a buffer containing 50 mM potassium phosphate (pH 2.6), 0.1 mM EDTA, 0.2 mM heptane sulfonic acid, and 10% methanol.…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%
“…Overexpression of a-syn in transfected DA and pheochromocytomic cell lines also reduces the activity of L-aromatic AADC, an enzyme which helps in the conversion of L-DOPA to dopamine, thereby reducing dopamine levels [70]. We can infer that one of the effects of a-syn is to regulate dopamine homeostasis by directly affecting the enzymes involved in the dopamine biosynthesis pathway.…”
Section: Somatic Monoamine Neurotransmission and Amyloid Diseasesmentioning
confidence: 94%